Peningkatan Keterampilan Pengolahan Otak-Otak Berbasis Surimi Ikan Patin: Pangan Sehat dan Higienis bagi Dasawisma PKK RT 26 Kelurahan Sungai Keledang - Farida Aryani; Adnan Putra Pratama; Mika Debora Br Barus; Elisa Ginsel Popang; Andi Lisnawati; Anis Syauqi; Muh Yamin; M Atta Bary (Universitas Muhammadiyah Semarang, 2025)
Food, as a basic human need, significantly determines the quality of life of the community. Catfish is a fairly abundant aquaculture commodity in East Kalimantan and has great potential as a raw material for food processing. In urban communities such as Sungai Keledang Village, Samarinda Seberang District, Samarinda City, the PKK (Family Welfare Movement) women's group plays a crucial role in maintaining household food security and is a potential actor in the development of a culinary-based creative economy. The main objective of this community service program is to increase the capacity of PKK RT 26 women in processing catfish-based food into healthy and hygienic surimi-based otak-otak products enriched with vegetables. The general implementation method of the activity includes preparation and coordination, mapping potential partners, training, evaluation, and program sustainability planning. The results of the activity were attended by approximately 25 housewives who are members of Dasawisma PKK RT 26. The presentation of material by the resource person explained functional foods, the benefits of catfish and its processed products, its vitamin content, and the processing techniques for surimi-based catfish otak-otak. The community was directly involved in every stage of the process, from preparing the ingredients, mixing them into a dough, adding the vegetables, cooking, and packaging, ensuring they understood the ratios of each ingredient used to make patin fish otak-otak. This activity improved the conceptual and technical knowledge of PKK Dasawisma RT 26 members in household food preparation.